GORDON RAMSAY’S POLITENESS STRATEGIES IN MASTERCHEF AND MASTERCHEF JUNIOR US - Safa, Annisa Friska; Kurniawan, Eri (Jurnal Pendidikan Bahasa dan Sastra, 2015)
AbstractThis research aims to investigate the types of politeness strategies that are performed by Gordon Ramsay in judging the Masterchef US and Masterchef Junior US contestants’ dishes and to reveal whether Gordon Ramsay performs any different politeness strategies between the Master chef and Masterchef Junior contestants. The data spring from Gordon Ramsay utterances, taken from the elimination test of two episodes of Masterchef season 4 (episode 9 and 12) and the elimination test of two episodes of Masterchef Junior US season 1 (episode 2 and 6). The framework of Brown Levinson’s (1987) politeness strategies is adopted. Findings reveal that Gordon Ramsay performed bald on-record strategy, positive politeness, and off record strategy. Furthermore, Ramsay performed diferent varieties of politeness strategies in Masterchef; and performed only positive politeness strategy in Masterchef Junior.Keywords: politeness strategies, masterchef, masterchef junior, Gordon RamsayAbstrakPenelitian ini bertujuan untuk menyelidiki tipe strategi kesopanan yang dilakukan oleh Gordon Ramsay saat menilai masakan dari kontestan Masterchefdan Masterchef Junior US dan untuk mengungkapkan adakah perbedaan strategi kesopanan yang dilakukan Gordon Ramsay kepada kontestan Masterchef US dan Masterchef Junior US. Data penelitian ini berupa tuturan Gordon Ramsay yang diambil dari tes eliminasi dalam dua episode Masterchef US musim ke-4 (episode 9 dan 12), dan dua episode Masterchef Junior US musim pertama (episode 2 dan 6). Teori yang digunakan adalah teori strategi kesopanan milik Brown dan Levinson (1987). Hasil temuan menunjukkan bahwa Gordon Ramsay melakukan strategi kesopanan bald-on record, strategi kesopanan positif, danstrategi kesopanan off record. Lebih lanjut, Gordon Ramsay melakukan lebih banyak variasi strategi kesopanan di Masterchef, sebaliknya, Gordon Ramsay hanya melakukan strategi kesopanan positif di Masterchef Junior.Kata-kata kunci: Strategi Kesopanan, Masterchef, Masterchef Junior,                    GordonRamsay